A bioinspired hydrogen bond-triggered ultrasensitive ionic mechanoreceptor skin - Vipin Amoli (Nature Portfolio, 2019)
Wearable pressure sensors have a range of potential applications. Here, the authors develop ion pairs decorated silica microstructures embedded in an elastomeric matrix to mimic natural skin mechanoreceptors’ functions for applications in pressure-sensitive artificial skin.